Alisher Navoi’s Ideas In The Education Of A Perfect Generation: The Experience Of New Uzbekistan - Uzakova Lola Abdurashitovna (Indonesian Journal Publisher, 2025)
This essay examines Alisher Navoi’s socio-ethical beliefs and his contribution to the development of a well-rounded person. Universal values like justice, truth, honesty, and humanism are artistically portrayed in Navoi’s works, underscoring their applicability in contemporary society. The article also explores the importance of Navoi’s legacy in youth education, emphasising his humanistic concepts and ethical teachings. The study focuses on how the philosopher’s theories can be incorporated into contemporary educational procedures to support the growth of morally and intellectually sophisticated people. In today’s globalised world, Navoi’s philosophy is still an essential resource for moral perfection and personal development, transcending his time. The article also looks at how these concepts fit into the systems of education and parenting that are in place today